HUBUNGAN KOMUNIKASI INTERPERSONAL DENGAN KEPUASAN KERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA BUKITTINGGI - Novia Gusliza (Universitas Negeri Padang, 2013)
This research aim to know satisfaction of, communications of interpersonal communications and of interpersonal with satisfaction of officer On duty Education of Young man and Athletics Town of Bukittinggi. This Research have the character of, research population amount to 100 people. this Research Sampel amount to 50 people with technique of Stratified Random Sampling. This Instrument Research enquette model scale of Likert. Result of data analysis indicate that 1) communications of interpersonal office On duty Education of Young man and Athletics Town of Bukittinggi reside in good category (73,08) 2) satisfaction of officer On Duty Education Of Young Man And Athletics Town of Bukittinggi reside in good category (70,08), and 3) there are meaning communications of interpersonal with satisfaction of officer On Duty Education Of Young Man And Athletics Town of Bukittinggi with t equal to 20,54 trust level 99%. Keywords: Interpersonal Communication, Job Satisfaction